The Potential Role of Inflammation in Modulating Endogenous Hippocampal Neurogenesis After Spinal Cord Injury - Sefiani, Arthur; Geoffroy, Cédric G. (Frontiers in Neuroscience, 2021)
Currently there are approximately 291,000 people suffering from a spinal cord injury (SCI) in the United States. SCI is associated with traumatic changes in mobility and neuralgia, as well as many other long-term chronic health complications, including metabolic disorders, diabetes mellitus, non-alcoholic steatohepatitis, osteoporosis, and elevated inflammatory markers. Due to medical advances, patients with SCI survive much longer than previously. This increase in life expectancy exposes them to novel neurological complications such as memory loss, cognitive decline, depression, and Alzheimer’s disease. In fact, these usually age-associated disorders are more prevalent in people living with SCI. A common factor of these disorders is the reduction in hippocampal neurogenesis. Inflammation, which is elevated after SCI, plays a major role in modulating hippocampal neurogenesis. While there is no clear consensus on the mechanism of the decline in hippocampal neurogenesis and cognition after SCI, we will examine in this review how SCI-induced inflammation could modulate hippocampal neurogenesis and provoke age-associated neurological disorders. Thereafter, we will discuss possible therapeutic options which may mitigate the influence of SCI associated complications on hippocampal neurogenesis.